Implementation of Ethnomathematics Strategy in Indonesian Traditional Games as Mathematics Learning Media - Zuhri Zuhri; Sinta Verawati Dewi; Jaka Wijaya Kusuma; Sri Rafiqoh; Isnaini Mahuda; Hamidah Hamidah (Yayasan Keluarga Guru Mandiri, 2023)
The learning strategy by associating cultural elements with mathematics is called ethnomathematics. The application of ethnomathematics in learning is very important in fostering a love for local culture which is currently almost abandoned due to modernization. This study aims to explain the mathematical elements contained in the Indonesian traditional game, namely engklek (hopscotch). The research method used ethnographic research. Data collection techniques used were observation, interviews, field notes, and documentation. The data analysis used was a triangulation analysis which consisted of data reduction, presentation, and drawing conclusions. The results of the study show that there are several mathematical topics in the game, including plane geometry, the concept of the relationship between angles (opposite angles and straight angles), cube net, congruence, the concept of reflection, the concept of mathematical logic, and the concept of probability. Hopscotch can be used as a medium for learning mathematics as a learning innovation in schools. The application of ethnomathematics strategies can improve elements of character education in the form of honesty, togetherness, and high sportsmanship in carrying out traditional games.